UNFAIR TERMS CONTROL IN CONTRACTS BETWEEN TRADERS (B2B) UNDER LITHUANIAN LAW - Balčiūnė, Aurelija (Teisė, 2017)
So far, the review of unfair terms has been harmonized in terms of contracts between traders and consumers (B2C), whereas the protection from unfair terms in contracts between traders (B2B) varies from country to country. This article is a contribution to the discussion of other authors related to the regulation of unfair terms in B2B contracts with a Lithuanian perspective taking into account the current Lithuanian legislation, foreign practice, “soft law” instruments, and unfair terms regulation in B2B contracts proposed by the draft Common European Sales Law (CESL).